Acrylic resin coating as well as preparation process and application thereof
By using homemade water-based acrylic resin emulsion and specific inorganic fillers in acrylic resin coatings, the problem of degradation of the coating's performance in humid environments is solved, and the water resistance, wear resistance and weather resistance of the coating is significantly improved, while maintaining the characteristics of environmental protection and simple process.
Patent Information
- Application Number
- CN202510327429.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-19
AI Technical Summary
When existing acrylic resin coatings are exposed to humid environments for a long time, the coating performance is prone to decline, and there are problems of insufficient water resistance and weather resistance.
The water-based acrylic resin emulsion is used and combined with specific inorganic fillers, such as SiO2/ZrO2 composite materials, talc powder and mica powder. Through multi-step chemical modification and introduction of composite materials, the water resistance, wear resistance and weather resistance of the coating are significantly improved.
It significantly improves the water resistance, wear resistance and weather resistance of the coating, while maintaining the characteristics of green and environmental protection and simple process.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to an acrylic resin coating and a preparation process and application thereof. Background Art
[0002] As an important material in modern industry, coatings have evolved from early natural vegetable oil and resin-based coatings to today's high-performance coatings with synthetic polymer materials as the core. Their development has been accompanied by human beings' continuous pursuit of environmental protection, performance and functionality. Among various types of coatings, acrylic resin coatings stand out due to their good comprehensive performance. They use acrylates and styrene as the main raw materials, obtain acrylic resins through copolymerization, and then process them into corresponding coating products. Acrylic resin coatings have the characteristics of good color retention, good decorative effect, low toxicity and environmental protection, and are widely used in construction, furniture decoration, automobile manufacturing and other fields. Especially after the rise of water-based coating technology, acrylic resin coatings have become one of the representatives of environmentally friendly coatings. Compared with traditional solvent-based coatings, water-based acrylic resin coatings are not only cheaper, but also safe to use, save resources and energy, and reduce environmental pollution.
[0003] At present, the preparation of acrylic resin coatings mainly includes solution polymerization, emulsion polymerization and other processes. Among them, solution polymerization is to dissolve the monomer in an organic solvent, carry out polymerization reaction under the action of an initiator, and finally form a uniform resin solution. This method is simple to operate and is suitable for the preparation of high molecular weight acrylic resins, but solvent volatilization will cause environmental pollution and waste of resources. Emulsion polymerization is to disperse the monomer in water, complete polymerization under the action of emulsifiers and initiators, and generate a stable emulsion coating. The coating produced by this method has the advantages of high solid content, fast drying speed and low cost, but there are also problems with insufficient water resistance and weather resistance, especially when exposed to a humid environment for a long time, the coating is prone to performance degradation.
[0004] In order to overcome the defects of existing acrylic resin coatings, researchers have also proposed a variety of improvement strategies. For example, by introducing nano-inorganic fillers such as nano-titanium dioxide, the thermal stability and mechanical strength of the coating can be significantly improved; by compounding with other functional resins, such as epoxy resin or polyurethane resin, the water resistance and wear resistance of the coating can be improved; in addition, adjusting the monomer ratio and polymerization process parameters are also important means to optimize the performance of the coating. However, these improvement measures still face many challenges. On the one hand, the addition of nano-inorganic fillers may increase production costs and may cause a decrease in the transparency and gloss of the coating; on the other hand, the compatibility problem between different components in the composite modification process has not been completely solved, which will affect the overall performance of the coating. Therefore, it is urgent to provide a new acrylic resin coating and its preparation method, which can comprehensively improve the comprehensive properties of the coating such as water resistance, wear resistance and weather resistance while ensuring environmental protection and simple process. Summary of the invention
[0005] The purpose of the present invention is to provide an acrylic resin coating, which adopts a homemade water-based acrylic resin emulsion and is matched with a specific inorganic filler, so that the coating is not only green and environmentally friendly, has strong adhesion, but also has good water resistance, weather resistance and wear resistance.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides an acrylic resin coating, comprising the following raw materials in parts by weight: 50-80 parts by weight of aqueous acrylic resin emulsion, 10-20 parts by weight of inorganic filler, 1-3 parts by weight of dispersant, 1-2 parts by weight of defoamer, 1-2 parts by weight of leveling agent, and 10-30 parts by weight of water.
[0007] Preferably, the method for preparing the aqueous acrylic resin emulsion comprises the following steps: The ethanol solution of tetraethyl orthosilicate and the n-butanol solution of tetrabutyl zirconate are sequentially added into ammonia water for reaction, filtered, dried and calcined to obtain SiO2 / ZrO2 composite material; the SiO2 / ZrO2 composite material is added into ethanol aqueous solution for ultrasonication, and then acrylamide propyl trimethoxysilane and citric acid aqueous solution are sequentially added for continuous ultrasonication, filtered and dried to obtain surface-treated SiO2 / ZrO2 composite material; 4,4′-diisocyanate dicyclohexylmethane and 1-hexadecanol are mixed, heated and stirred, and then the surface-treated SiO2 / ZrO2 composite material and dibutyltin dilaurate are added for continuous stirring, filtered and dried to obtain water-resistant modified SiO2 / ZrO2 composite material; Ethylene glycol ether, 3-perfluorobutyl propanol and water-resistant modified SiO2 / ZrO2 composite material are mixed, heated and stirred, and then ethyl methacrylate, butyl acrylate, hydroxyethyl acrylate, methacrylamide, acrylic acid and azobisisobutyronitrile are added and stirred continuously. After the mixture is cooled, dimethylethanolamine and water are added and stirred, and cooled to obtain a water-based acrylic resin emulsion.
[0008] The aqueous acrylic resin emulsion prepared by the method is not only green and environmentally friendly, but also has strong adhesion and can significantly improve the water resistance, abrasion resistance and weather resistance of the coating.
[0009] The preparation method of the water-based acrylic resin emulsion in the present invention significantly improves the water resistance, wear resistance and weather resistance of the coating through multi-step chemical modification and introduction of composite materials. First, the SiO2 / ZrO2 composite material is generated by reacting ethyl orthosilicate with tetrabutyl zirconate in an ammonia environment. The material has high mechanical strength and stability and can enhance the water resistance and wear resistance of the coating. Secondly, the SiO2 / ZrO2 composite material is surface modified by acrylamide propyl trimethoxysilane, and active functional groups are introduced to improve its compatibility and dispersibility with organic polymers. Then, by reacting 4,4′-diisocyanate dicyclohexylmethane with 1-hexadecanol, a long-chain alkyl structure is introduced into the surface of the composite material, further enhancing the hydrophobicity and reducing the contact area of water molecules, thereby improving the water resistance. At the same time, the addition of 3-perfluorobutyl propanol provides the system with a perfluorocarbon chain with extremely low surface energy, effectively inhibiting the penetration of water molecules, while preventing erosion by other substances, and enhancing the weather resistance of the coating. Finally, during the polymerization process, monomers such as ethyl methacrylate and butyl acrylate react with the above-mentioned modified composite materials to form a dense cross-linked network structure, which makes the coating both flexible and hard, and significantly improves the wear resistance.
[0010] Preferably, the weight ratio of the ethanol solution of ethyl orthosilicate to the n-butanol solution of tetrabutyl zirconate is 40-60:30-50; The weight ratio of the SiO2 / ZrO2 composite material to acrylamidopropyltrimethoxysilane is 2-8:1.5-2; The weight ratio of the 4,4′-diisocyanate dicyclohexylmethane, 1-hexadecanol, and surface treated SiO2 / ZrO2 composite material is (3-7): (1-3.5): (2-4); The weight ratio of the 3-perfluorobutyl propanol and the water-resistant modified SiO2 / ZrO2 composite material is 1-3:2-6; The weight ratio of ethyl methacrylate, butyl acrylate, hydroxyethyl acrylate, methacrylamide and acrylic acid is (5-10): (2-4): (2-4): (2-4): (1-3).
[0011] Furthermore, the preparation method of the aqueous acrylic resin emulsion comprises the following steps: Under the stirring conditions of 35-40°C and 200-300r / min, 40-60 parts by weight of ethyl orthosilicate ethanol solution and 30-50 parts by weight of tetrabutyl zirconate n-butanol solution are sequentially added to 100-200 parts by weight of ammonia water for reaction for 7-15h, filtered, dried, and then calcined for 1-3h to obtain SiO2 / ZrO2 composite material; 2-8 parts by weight of SiO2 / ZrO2 composite material is added to 40-60 parts by weight of ethanol aqueous solution and ultrasonicated for 40-50min, and then 1.5-2 parts by weight of acrylamidopropyltrimethoxysilane and 1-1.5 parts by weight of citric acid are sequentially added; The citric acid aqueous solution is ultrasonicated for 50-60 minutes, filtered, and dried to obtain a surface-treated SiO2 / ZrO2 composite material; 3-7 parts by weight of 4,4′-diisocyanate dicyclohexylmethane and 1-3.5 parts by weight of 1-hexadecanol are mixed, stirred at 80-85°C and 100-200r / min for 30-50 minutes, and then 2-4 parts by weight of the surface-treated SiO2 / ZrO2 composite material and 0.05-0.1 parts by weight of dibutyltin dilaurate are added and stirred for 10-20 hours, filtered, and dried to obtain a water-resistant modified SiO2 / ZrO2 composite material; 1-5 parts by weight of ethylene glycol ethyl ether, 1-3 parts by weight of 3-perfluorobutyl propanol and 2-6 parts by weight of water-resistant modified SiO2 / ZrO2 composite material are mixed, stirred at 100-150°C and 100-300r / min for 1-3h, then 5-10 parts by weight of ethyl methacrylate, 2-4 parts by weight of butyl acrylate, 2-4 parts by weight of hydroxyethyl acrylate, 1-3 parts by weight of methacrylamide, 1-3 parts by weight of acrylic acid and 0.5-1.5 parts by weight of azobisisobutyronitrile are added, and stirring is continued for 5-10h. After the mixture is cooled to 80-90°C, 0.5-1 parts by weight of dimethylethanolamine and 10-30 parts of water are added, stirred for 3-5h, and cooled to room temperature to obtain an aqueous acrylic resin emulsion.
[0012] Preferably, the concentration of the ethanol solution of tetraethyl orthosilicate is 20-25wt%.
[0013] Preferably, the concentration of the tetrabutyl zirconate n-butanol solution is 10-20wt%.
[0014] Preferably, the concentration of the ammonia water is 12-18wt%.
[0015] Preferably, the concentration of the ethanol aqueous solution is 50-65wt%.
[0016] Preferably, the concentration of the citric acid aqueous solution is 8-12wt%.
[0017] Preferably, the calcination temperature is 500-600°C.
[0018] Preferably, the power of the ultrasound is 100-200W and the frequency is 30-50kHz.
[0019] Preferably, the inorganic filler is one or a mixture of two or more of titanium dioxide, calcium carbonate, talcum powder, kaolin and mica powder.
[0020] The present invention also uses a specific combination of inorganic fillers to be used together with the above-mentioned water-based acrylic resin emulsion, thereby further improving the wear resistance and water resistance of the coating. Among them, talcum powder has good lubricity and dispersibility, can improve the flexibility of the coating and reduce internal stress, and mica powder has a flaky structure, can form a dense barrier in the coating, and enhance the anti-penetration ability. Under the synergistic effect of the two, talcum powder improves the smoothness and construction performance of the coating, while mica powder strengthens the density and mechanical strength of the coating, thereby effectively preventing water penetration and reducing external friction damage, and finally achieving further improvement of wear resistance and water resistance.
[0021] Furthermore, the inorganic filler is a mixture of titanium dioxide, talcum powder and mica powder in a weight ratio of 10:(1-3):(2-4).
[0022] Preferably, the dispersant is any one of dispersant EDAPLAN® 516, dispersant EDAPLAN® 492, and dispersant EDAPLAN® 397 (Mingling, Germany).
[0023] Preferably, the defoamer is any one of defoamer BYK-024, defoamer BYK-012 and defoamer BYK-019 (BYK, Germany).
[0024] Preferably, the leveling agent is any one of leveling agent Tego-410, leveling agent Tego-432, and leveling agent Tego-450 (produced by Germany Digo).
[0025] The present invention provides a process for preparing an acrylic resin coating, comprising the following steps: Weigh the raw materials according to the formula, mix the water-based acrylic resin emulsion, inorganic filler, dispersant and water, stir for 20-40 minutes at 25-35° C. and 400-600 r / min, then add the defoamer and leveling agent and continue stirring for 10-30 minutes, cool to room temperature, and obtain the acrylic resin coating.
[0026] The present invention also provides application of the acrylic resin coating in the fields of construction and decoration.
[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention provides an acrylic resin coating and a preparation method thereof, wherein a self-made water-based acrylic resin emulsion is used in the raw material formula and matched with a specific inorganic filler, wherein the water-based acrylic resin emulsion is made by reacting ethylene glycol ethyl ether, 3-perfluorobutyl propanol, a water-resistant modified SiO2 / ZrO2 composite material, acrylic monomer and water, which further improves the water resistance, weather resistance, wear resistance and adhesion of the coating, and is green and environmentally friendly with stable performance. The present invention also provides a preparation process of the above acrylic resin coating and its application in the fields of construction and decoration.
[0028] 2. The water-based acrylic resin emulsion prepared by the present invention significantly improves the water resistance, wear resistance and weather resistance of the coating through multi-step chemical modification and the introduction of composite materials. Among them, the SiO2 / ZrO2 composite material has high mechanical strength and stability, which can enhance the water resistance and wear resistance of the coating. By reacting 4,4′-diisocyanate dicyclohexylmethane with 1-hexadecanol, a long-chain alkyl structure is introduced into the surface of the composite material, further enhancing the hydrophobicity and reducing the contact area of water molecules, thereby improving the water resistance. The addition of 3-perfluorobutyl propanol provides the system with a perfluorocarbon chain with extremely low surface energy, effectively inhibiting the penetration of water molecules, while preventing erosion by other substances, and enhancing the weather resistance of the coating.
[0029] 3. The present invention adopts a specific combination of inorganic fillers to be used in combination with the above-mentioned aqueous acrylic resin emulsion, wherein talcum powder has good lubricity and dispersibility, can improve the flexibility of the coating and reduce internal stress, and mica powder can form a dense barrier in the coating to enhance the anti-penetration ability. Under the synergistic effect of the two, talcum powder improves the smoothness and construction performance of the coating, while mica powder enhances the density and mechanical strength of the coating, thereby effectively preventing water penetration and reducing external friction damage, further improving the wear resistance and water resistance of the coating. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1 This embodiment provides an acrylic resin coating, which is composed of the following raw materials in parts by weight: 65 parts by weight of aqueous acrylic resin emulsion, 15 parts by weight of inorganic filler, 2 parts by weight of dispersant, 1.5 parts by weight of defoamer, 1.5 parts by weight of leveling agent, and 20 parts by weight of water. The dispersant is dispersant EDAPLAN® 516; the defoamer is defoamer BYK-024; and the leveling agent is leveling agent Tego-410.
[0032] The inorganic filler is a mixture of titanium dioxide, talc and mica powder in a weight ratio of 10:2:3. The average particle size of titanium dioxide is 0.5 μm, purchased from Tianjin Linyi Chemical Technology Co., Ltd.; the average particle size of talc is 10 μm, purchased from Hubei Tuobang Chemical Co., Ltd.; the average particle size of mica powder is 15 μm, purchased from Wuhan Jiyesheng Chemical Co., Ltd.
[0033] The preparation method of the aqueous acrylic resin emulsion comprises the following steps: Under the stirring conditions of 37°C and 250r / min, 50 parts by weight of 24wt% ethyl orthosilicate ethanol solution and 40 parts by weight of 15wt% tetrabutyl zirconate n-butanol solution were added to 160 parts by weight of 15wt% ammonia water in sequence for reaction for 10h, filtered, dried, and then calcined at 550°C for 2h to obtain SiO2 / ZrO2 composite material; 5 parts by weight of SiO2 / ZrO2 composite material were added to 50 parts by weight of 60wt% ethanol aqueous solution, ultrasonicated for 45min under the conditions of ultrasonic power of 150W and ultrasonic frequency of 40kHz, and then 1.8 parts by weight of SiO2 / ZrO2 composite material were added in sequence. 1.2 parts by weight of acrylamide propyl trimethoxysilane and 10wt% citric acid aqueous solution are ultrasonically treated for 55 minutes, filtered, and dried to obtain a surface-treated SiO2 / ZrO2 composite material; 5 parts by weight of 4,4′-diisocyanate dicyclohexylmethane are mixed with 3 parts by weight of 1-hexadecanol, stirred at 82°C and 120r / min for 40 minutes, and then 3 parts by weight of the surface-treated SiO2 / ZrO2 composite material and 0.06 parts by weight of dibutyltin dilaurate are added and stirred for 15 hours, filtered, and dried to obtain a water-resistant modified SiO2 / ZrO2 composite material; Mix 3 parts by weight of ethylene glycol ethyl ether, 2 parts by weight of 3-perfluorobutyl propanol and 4 parts by weight of water-resistant modified SiO2 / ZrO2 composite material, stir at 120°C and 200 r / min for 2 hours, then add 8 parts by weight of ethyl methacrylate, 3 parts by weight of butyl acrylate, 3 parts by weight of hydroxyethyl acrylate, 2 parts by weight of methacrylamide, 2 parts by weight of acrylic acid and 1 part by weight of azobisisobutyronitrile, and continue stirring for 6 hours. After cooling to 85°C, add 0.8 parts by weight of dimethylethanolamine and 20 parts of water, stir for 4 hours, and cool to room temperature to obtain a water-based acrylic resin emulsion.
[0034] This embodiment provides a preparation process of an acrylic resin coating, comprising the following steps: Weigh the raw materials according to the formula, mix the water-based acrylic resin emulsion, inorganic filler, dispersant and water, stir for 30 minutes at 30° C. and 500 r / min, then add the defoamer and leveling agent and continue stirring for 20 minutes, cool to room temperature, and obtain the acrylic resin coating.
[0035] Example 2 This embodiment provides an acrylic resin coating, which is composed of the following raw materials in parts by weight: 50 parts by weight of aqueous acrylic resin emulsion, 10 parts by weight of inorganic filler, 1 part by weight of dispersant, 1 part by weight of defoamer, 1 part by weight of leveling agent, and 10 parts by weight of water. The dispersant is dispersant EDAPLAN® 516; the defoamer is defoamer BYK-024; and the leveling agent is leveling agent Tego-410.
[0036] The inorganic filler is a mixture of titanium dioxide, talcum powder and mica powder in a weight ratio of 10:1:4. The average particle size of titanium dioxide is 0.5 μm, purchased from Tianjin Linyi Chemical Technology Co., Ltd.; the average particle size of talcum powder is 10 μm, purchased from Hubei Tuobang Chemical Co., Ltd.; the average particle size of mica powder is 15 μm, purchased from Wuhan Jiyesheng Chemical Co., Ltd.
[0037] The preparation method of the aqueous acrylic resin emulsion is the same as that of Example 1.
[0038] This embodiment provides a preparation process of an acrylic resin coating, comprising the following steps: Weigh the raw materials according to the formula, mix the water-based acrylic resin emulsion, inorganic filler, dispersant and water, stir for 20 minutes at 25° C. and 400 r / min, then add the defoamer and leveling agent and continue stirring for 30 minutes, cool to room temperature, and obtain the acrylic resin coating.
[0039] Example 3 This embodiment provides an acrylic resin coating, which is composed of the following raw materials in parts by weight: 80 parts by weight of aqueous acrylic resin emulsion, 20 parts by weight of inorganic filler, 3 parts by weight of dispersant, 2 parts by weight of defoamer, 2 parts by weight of leveling agent, 30 parts by weight of water. The dispersant is dispersant EDAPLAN®516; the defoamer is defoamer BYK-024; the leveling agent is leveling agent Tego-410.
[0040] The inorganic filler is a mixture of titanium dioxide, talcum powder and mica powder in a weight ratio of 10:3:2. The average particle size of titanium dioxide is 0.5 μm, purchased from Tianjin Linyi Chemical Technology Co., Ltd.; the average particle size of talcum powder is 10 μm, purchased from Hubei Tuobang Chemical Co., Ltd.; the average particle size of mica powder is 15 μm, purchased from Wuhan Jiyesheng Chemical Co., Ltd.
[0041] The preparation method of the aqueous acrylic resin emulsion is the same as that of Example 1.
[0042] This embodiment provides a preparation process of an acrylic resin coating, comprising the following steps: Weigh the raw materials according to the formula, mix the water-based acrylic resin emulsion, inorganic filler, dispersant and water, stir for 40 minutes at 35° C. and 600 r / min, then add the defoamer and leveling agent and continue stirring for 10 minutes, cool to room temperature, and obtain the acrylic resin coating.
[0043] Comparative Example 1 The difference between this comparative example and Example 1 is that the preparation method of the aqueous acrylic resin emulsion is different, which is as follows: the preparation method of the aqueous acrylic resin emulsion comprises the following steps: Under stirring conditions of 37° C. and 250 r / min, 50 parts by weight of a 24wt% ethanol solution of tetraethyl orthosilicate and 40 parts by weight of a 15wt% n-butanol solution of tetrabutyl zirconate were sequentially added to 160 parts by weight of 15wt% ammonia water, reacted for 10 hours, filtered, dried, and then calcined at 550° C. for 2 hours to obtain a SiO2 / ZrO2 composite material; Mix 3 parts by weight of ethylene glycol ethyl ether, 2 parts by weight of 3-perfluorobutyl propanol and 4 parts by weight of SiO2 / ZrO2 composite material, stir at 120°C and 200 r / min for 2 hours, then add 8 parts by weight of ethyl methacrylate, 3 parts by weight of butyl acrylate, 3 parts by weight of hydroxyethyl acrylate, 2 parts by weight of methacrylamide, 2 parts by weight of acrylic acid and 1 part by weight of azobisisobutyronitrile, and continue stirring for 6 hours. After cooling to 85°C, add 0.8 parts by weight of dimethylethanolamine and 20 parts of water, stir for 4 hours, and cool to room temperature to obtain an aqueous acrylic resin emulsion.
[0044] Comparative Example 2 The difference between this comparative example and Example 1 is that the preparation method of the aqueous acrylic resin emulsion is different, which is as follows: the preparation method of the aqueous acrylic resin emulsion comprises the following steps: Under stirring conditions of 37°C and 250r / min, 50 parts by weight of 24wt% ethyl orthosilicate ethanol solution and 40 parts by weight of 15wt% tetrabutyl zirconate n-butanol solution are sequentially added to 160 parts by weight of 15wt% ammonia water for reaction for 10h, filtered, dried, and then calcined at 550°C for 2h to obtain a SiO2 / ZrO2 composite material; 5 parts by weight of 4,4′-diisocyanate dicyclohexylmethane and 3 parts by weight of 1-hexadecanol are mixed, stirred at 82°C and 120r / min for 40min, and then 3 parts by weight of SiO2 / ZrO2 composite material and 0.06 parts by weight of dibutyltin dilaurate are added and stirred for 15h, filtered, dried, and a water-resistant modified SiO2 / ZrO2 composite material is obtained; Mix 3 parts by weight of ethylene glycol ethyl ether, 2 parts by weight of 3-perfluorobutyl propanol and 4 parts by weight of water-resistant modified SiO2 / ZrO2 composite material, stir at 120°C and 200 r / min for 2 hours, then add 8 parts by weight of ethyl methacrylate, 3 parts by weight of butyl acrylate, 3 parts by weight of hydroxyethyl acrylate, 2 parts by weight of methacrylamide, 2 parts by weight of acrylic acid and 1 part by weight of azobisisobutyronitrile, and continue stirring for 6 hours. After cooling to 85°C, add 0.8 parts by weight of dimethylethanolamine and 20 parts of water, stir for 4 hours, and cool to room temperature to obtain a water-based acrylic resin emulsion.
[0045] Comparative Example 3 The difference between this comparative example and Example 1 is that the preparation method of the aqueous acrylic resin emulsion is different, which is as follows: the preparation method of the aqueous acrylic resin emulsion comprises the following steps: 5 parts by weight of nano-silica are added to 50 parts by weight of 60wt% ethanol aqueous solution, and ultrasonicated for 45 minutes under the conditions of ultrasonic power of 150W and ultrasonic frequency of 40kHz, and then 1.8 parts by weight of acrylamide propyl trimethoxy silane and 1.2 parts by weight of 10wt% citric acid aqueous solution are added in sequence, and ultrasonicated for 55 minutes, filtered, and dried to obtain surface-treated nano-silica; 5 parts by weight of 4,4′-diisocyanate dicyclohexylmethane and 3 parts by weight of 1-hexadecanol are mixed, stirred for 40 minutes at 82°C and 120r / min, and then 3 parts by weight of surface-treated nano-silica and 0.06 parts by weight of dibutyltin dilaurate are added, and stirring is continued for 15 hours, filtered, and dried to obtain water-resistant modified nano-silica; wherein the average particle size of the nano-silica is 50nm; Mix 3 parts by weight of ethylene glycol ethyl ether, 2 parts by weight of 3-perfluorobutyl propanol and 4 parts by weight of water-resistant modified nano-silica, stir for 2 hours at 120°C and 200 r / min, then add 8 parts by weight of ethyl methacrylate, 3 parts by weight of butyl acrylate, 3 parts by weight of hydroxyethyl acrylate, 2 parts by weight of methacrylamide, 2 parts by weight of acrylic acid and 1 part by weight of azobisisobutyronitrile, and continue stirring for 6 hours. After the mixture is cooled to 85°C, 0.8 parts by weight of dimethylethanolamine and 20 parts of water are added, stirred for 4 hours, and cooled to room temperature to obtain an aqueous acrylic resin emulsion.
[0046] Comparative Example 4 The difference between this comparative example and Example 1 is that the preparation method of the aqueous acrylic resin emulsion is different, which is as follows: the preparation method of the aqueous acrylic resin emulsion comprises the following steps: Under the stirring conditions of 37°C and 250r / min, 50 parts by weight of 24wt% ethyl orthosilicate ethanol solution and 40 parts by weight of 15wt% tetrabutyl zirconate n-butanol solution were added to 160 parts by weight of 15wt% ammonia water in sequence for reaction for 10h, filtered, dried, and then calcined at 550°C for 2h to obtain SiO2 / ZrO2 composite material; 5 parts by weight of SiO2 / ZrO2 composite material were added to 50 parts by weight of 60wt% ethanol aqueous solution, ultrasonicated for 45min under the conditions of ultrasonic power of 150W and ultrasonic frequency of 40kHz, and then 1.8 parts by weight of SiO2 / ZrO2 composite material were added in sequence. 1.2 parts by weight of acrylamide propyl trimethoxysilane and 10wt% citric acid aqueous solution are ultrasonically treated for 55 minutes, filtered, and dried to obtain a surface-treated SiO2 / ZrO2 composite material; 5 parts by weight of 4,4′-diisocyanate dicyclohexylmethane are mixed with 3 parts by weight of 1-hexadecanol, stirred at 82°C and 120r / min for 40 minutes, and then 3 parts by weight of the surface-treated SiO2 / ZrO2 composite material and 0.06 parts by weight of dibutyltin dilaurate are added and stirred for 15 hours, filtered, and dried to obtain a water-resistant modified SiO2 / ZrO2 composite material; Mix 3 parts by weight of ethylene glycol ethyl ether with 4 parts by weight of water-resistant modified SiO2 / ZrO2 composite material, stir at 120°C and 200 r / min for 2 hours, then add 8 parts by weight of ethyl methacrylate, 3 parts by weight of butyl acrylate, 3 parts by weight of hydroxyethyl acrylate, 2 parts by weight of methacrylamide, 2 parts by weight of acrylic acid and 1 part by weight of azobisisobutyronitrile, and continue stirring for 6 hours. After cooling to 85°C, add 0.8 parts by weight of dimethylethanolamine and 20 parts of water, stir for 4 hours, and cool to room temperature to obtain a water-based acrylic resin emulsion.
[0047] Comparative Example 5 The difference between this comparative example and Example 1 is that the inorganic filler is different, specifically as follows: the inorganic filler is a mixture of titanium dioxide and mica powder in a weight ratio of 10:5; wherein the average particle size of the titanium dioxide is 0.5 μm, and the average particle size of the mica powder is 15 μm.
[0048] Comparative Example 6 The difference between this comparative example and Example 1 is that the inorganic filler is different, specifically as follows: the inorganic filler is a mixture of titanium dioxide and talcum powder in a weight ratio of 10:5; wherein the average particle size of the titanium dioxide is 0.5 μm, and the average particle size of the talcum powder is 10 μm.
[0049] Performance Testing The acrylic resin coating obtained in the above examples 1-3 and comparative examples 1-6 was applied to the surface of a polypropylene substrate and tested after curing (the coating thickness was 30 μm). Adhesion was measured with reference to the national standard GB / T 9286-2021 (0-5 grades, 5 grades were the worst). Abrasion resistance was measured with reference to the national standard GB / T 1768-2006. Neutral salt spray resistance was measured with reference to the national standard GB / T 1771-2007, acid resistance (50 g / L sulfuric acid solution, 72 h), and alkali resistance (50 g / L sodium hydroxide solution, 72 h). Water resistance was measured with reference to the national standard GB / T 1733-1993, and the above acrylic resin coating was applied to the surface of a wood block. After curing (the coating thickness was 30 μm), it was immersed in 25°C water for 1 day, and the mass change before and after the wood block was taken out to measure the water absorption rate to evaluate the water resistance, and the presence or absence of wrinkles and damage to the coating was recorded. The results are shown in Table 1.
[0050] Table 1: Performance test results of acrylic resin coatings
[0051] It can be seen from the above performance test results that the acrylic resin coatings prepared in Examples 1-3 have good adhesion, wear resistance, weather resistance and water resistance, especially the acrylic resin coating prepared in Example 1 has the most outstanding comprehensive performance. This is because the present invention significantly improves the adhesion, wear resistance, weather resistance and water resistance of the acrylic resin coating by using a homemade water-based acrylic resin emulsion and matching a specific inorganic filler. Comparative Examples 1-6 Compared with Examples 1-3, Comparative Examples 1-4 do not use a water-based acrylic resin emulsion prepared by a specific method, and Comparative Examples 5-6 do not use a specific combination of inorganic fillers. From the results, it can be seen that this leads to a significant decrease in the comprehensive performance of the acrylic resin coating. The above experimental results further prove the importance of the corresponding technical solutions in Examples 1-3 of the present invention for their technical effects.
[0052] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An acrylic resin coating, characterized in that: Including the following ingredients: In parts by weight, the invention comprises 50-80 parts of water-based acrylic resin emulsion, 10-20 parts of inorganic filler, 1-3 parts of dispersant, 1-2 parts of defoamer, 1-2 parts of leveling agent and 10-30 parts of water; the water-based acrylic resin emulsion is prepared by reacting ethylene glycol ethyl ether, 3-perfluorobutyl propanol, water-resistant modified SiO2 / ZrO2 composite material, acrylic acid monomer and water.
2. The acrylic resin coating according to claim 1, characterized in that: The preparation method of the aqueous acrylic resin emulsion comprises the following steps: The ethanol solution of tetraethyl orthosilicate and the n-butanol solution of tetrabutyl zirconate are sequentially added into ammonia water for reaction, filtered, dried and calcined to obtain SiO2 / ZrO2 composite material; the SiO2 / ZrO2 composite material is added into ethanol aqueous solution for ultrasonication, and then acrylamide propyl trimethoxysilane and citric acid aqueous solution are sequentially added for continuous ultrasonication, filtered and dried to obtain surface-treated SiO2 / ZrO2 composite material; 4,4′-diisocyanate dicyclohexylmethane and 1-hexadecanol are mixed, heated and stirred, and then the surface-treated SiO2 / ZrO2 composite material and dibutyltin dilaurate are added for continuous stirring, filtered and dried to obtain water-resistant modified SiO2 / ZrO2 composite material; Ethylene glycol ether, 3-perfluorobutyl propanol and water-resistant modified SiO2 / ZrO2 composite material are mixed, heated and stirred, and then ethyl methacrylate, butyl acrylate, hydroxyethyl acrylate, methacrylamide, acrylic acid and azobisisobutyronitrile are added and stirred continuously. After the mixture is cooled, dimethylethanolamine and water are added and stirred, and cooled to obtain a water-based acrylic resin emulsion.
3. The acrylic resin coating according to claim 2, characterized in that: The weight ratio of the ethanol solution of ethyl orthosilicate to the n-butanol solution of tetrabutyl zirconate is 40-60:30-50; The weight ratio of the SiO2 / ZrO2 composite material to acrylamidopropyltrimethoxysilane is 2-8:1.5-2; The weight ratio of the 4,4′-diisocyanate dicyclohexylmethane, 1-hexadecanol, and surface treated SiO2 / ZrO2 composite material is (3-7): (1-3.5): (2-4); The weight ratio of the 3-perfluorobutyl propanol and the water-resistant modified SiO2 / ZrO2 composite material is 1-3:2-6; The weight ratio of ethyl methacrylate, butyl acrylate, hydroxyethyl acrylate, methacrylamide and acrylic acid is (5-10): (2-4): (2-4): (2-4): (1-3).
4. The acrylic resin coating according to claim 1, characterized in that: The inorganic filler is one or a mixture of two or more of titanium dioxide, calcium carbonate, talcum powder, kaolin and mica powder.
5. The acrylic resin coating according to claim 4, characterized in that: The inorganic filler is a mixture of titanium dioxide, talcum powder and mica powder in a weight ratio of 10:(1-3):(2-4).
6. The acrylic resin coating according to claim 1, characterized in that: The dispersant is any one of dispersant EDAPLAN®516, dispersant EDAPLAN®492 and dispersant EDAPLAN®397.
7. The acrylic resin coating according to claim 1, characterized in that: The defoamer is any one of defoamer BYK-024, defoamer BYK-012 and defoamer BYK-019.
8. The acrylic resin coating according to claim 1, characterized in that: The leveling agent is any one of leveling agent Tego-410, leveling agent Tego-432, and leveling agent Tego-450.
9. A process for preparing an acrylic resin coating as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: Weigh the raw materials according to the formula, mix the water-based acrylic resin emulsion, inorganic filler, dispersant and water, stir for 20-40 minutes at 25-35° C. and 400-600 r / min, then add the defoamer and leveling agent and continue stirring for 10-30 minutes, cool to room temperature, and obtain the acrylic resin coating.
10. Use of the acrylic resin coating according to any one of claims 1 to 8 in the field of construction or decoration.
Citation Information
Patent Citations
Preparation of high performance metal protection nano coating
CN101486869A
Two-component high-hardness waterborne wood paint
CN102732115A
Corrosion-resistant varnish
CN104559548A
Coating for indoor decoration
CN105273541A
Preparation method of coating composition
CN108822589A
Cited By
Multifunctional coating based on acrylic resin and production process thereof
CN120484589A